A Descriptive study between Iraqi EFL Learners and English Native Speakers in Pronouncing English Vowels: A Contrastive Study - Furqan Altaie (collage of education / university of Misan, 2021)
Iraqi speakers of English face some phonetic and phonological difficulties that are related to the production of different speech sounds especially English vowel sounds. The difficulty in producing these sounds is related to several matters. Firstly, the complex orthographic system of English. Secondly is the inconsistent relationship between spelling and pronunciation. Third shows the differences between the two different sound systems (Arabic and English). The regional differences and the effect of the native language on the second language can be considered as two of the real problems in pronunciation.